2015
DOI: 10.1530/eje-13-0907
|View full text |Cite
|
Sign up to set email alerts
|

Transient neonatal hyperthyrotropinemia is a risk factor for developing persistent hyperthyrotropinemia in childhood with repercussion on developmental status

Abstract: Objective: Transient neonatal hyperthyrotropinemia (TNH) is defined as a neonatal abnormality of thyroid function, which reverts to normal at re-examination after 2 weeks of life. The thyroid function of these infants has not been sufficiently studied in terms of the risk of developing persistent hyperthyrotropinemia (PH) in later childhood and its impact on growth and development. Design: A prospective cohort study included all babies born in our hospital between 2001 and 2006 and screened for hypothyroidism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
13
4
Order By: Relevance
“…The natural history of transiently raised levels of thyroid-stimulating hormone (TSH), with or without associated low thyroxine (T4) levels, in preterm infants is complex and affected by factors such as maternal iodine status,1 developmental immaturity of endocrine systems,2–5 critical illness6 and drug exposure 7. The incidence of mildly raised TSH levels depends on the definition, denominator and age-group studied, but in population studies it has been reported as 3.3%8 and 6%,9 and in selected clinical studies, as high as 22.3% 10. There is no consensus on whether subtle thyroid dysfunction should be treated11 12 and its long-term consequences are unclear, as studies are typically methodologically restricted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural history of transiently raised levels of thyroid-stimulating hormone (TSH), with or without associated low thyroxine (T4) levels, in preterm infants is complex and affected by factors such as maternal iodine status,1 developmental immaturity of endocrine systems,2–5 critical illness6 and drug exposure 7. The incidence of mildly raised TSH levels depends on the definition, denominator and age-group studied, but in population studies it has been reported as 3.3%8 and 6%,9 and in selected clinical studies, as high as 22.3% 10. There is no consensus on whether subtle thyroid dysfunction should be treated11 12 and its long-term consequences are unclear, as studies are typically methodologically restricted.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on whether subtle thyroid dysfunction should be treated11 12 and its long-term consequences are unclear, as studies are typically methodologically restricted. It has been suggested that infants with transiently raised TSH levels may have a high risk of subclinical hypothyroidism in childhood4 13 and possibly developmental delay,9 although this is not a consistent observation 5 14. The most common neonatal thyroid dysfunction in preterm infants is hypothyroxinaemia (low T4 with normal TSH levels), with an incidence of between 7% and 100%15 in infants <28 weeks’ gestation; the wide range of reported incidence reflects varying definitions and methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…TSH levels tend to be higher in newborns with a lower GA which reverts to normality at re-examination after 2 weeks (25,26). Although one multicenter study reported tranisient HTT is a risk factor of developing persistent HTT in children with neurodevelopment delays (27), our results revealed that HTT in our study reverts to normality without neurodevelopmental consequences. It was GA, but not thyroid function, determined the long-term neurological outcomes in our premature infants.…”
Section: Discussionmentioning
confidence: 42%
“…As TSH is the most sensitive indicator of thyroid function, LT4 treatments are recommended in case of consistently elevated TSH levels. One study reported that neonatal hyperthyrotropinemia was a risk factor for persis tent hyperthyrotropinemia accompanied with developmental delay 10). Hyperthyrotropinemia observed in premature infants was also related to longterm developmental delays, while other studies reported that early termination of treatment was possible in most infants 3840)…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, it is difficult to determine the factors that contribute to this delayed development since hospitalization criteria for these patients differ across units 8,9) and these infants are often not followed. A study conducted by Cuestas et al 10) showed that these infants are significantly disadvantaged due to the longterm effects of hyperthyrotropinemia that persist until childhood.…”
Section: Introductionmentioning
confidence: 99%